In-situ analysis detection method and device for electrical contact surface film damage

In-situ analysis and detection of surface film damage of electrical contacts through elliptical polarization technology, the problems of high cost and long detection cycle of existing detection methods are solved, and fast, accurate and lossless surface film damage detection of electrical contacts is achieved, which improves the reliability and service life of electrical devices.

CN119757232APending Publication Date: 2025-04-04XIAMEN UNIV OF TECH

Patent Information

Application Number
CN202411813710.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing electrical contact detection methods are costly and have a long detection cycle, making it difficult to accurately detect damage to the surface film of the electrical contact, affecting the reliability and service life of electrical devices.

Method used

Elliptical polarization technology is used to conduct in-situ analysis and detection of surface film damage of electrical contacts, and the changes in surface materials of electrical contacts are accurately detected through elliptical polarization spectral testing and fitting analysis.

Benefits of technology

It realizes rapid, accurate and non-destructive testing of surface membrane damage of electrical contacts, reduces detection costs, improves detection efficiency, and helps optimize the maintenance plan of electrical equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119757232A_ABST
    Figure CN119757232A_ABST
Patent Text Reader

Abstract

The invention relates to an in-situ analysis detection method and device for electrical contact surface film damage. The in-situ analysis detection method comprises the following steps: 1) adjusting the height and angle of a sample test platform to a proper position; 2) switching on an electric contact test platform circuit, simulating an in-situ working process of an electric contact, and obtaining electric contact information and elliptically polarized light detection information; (3) transmitting polarized light detection information to light source acquisition equipment, and (4) establishing a proper physical optical model and a vibrator model, and performing data fitting analysis to obtain the in-situ change condition of the surface of the electrical contact. By adopting a non-contact in-situ spectrum testing technology, the early-stage in-situ failure process of the electrical contact is accurately, quickly and nondestructively detected in real time, and an equipment means and a test basis are provided for research on an electrical contact early-stage failure mechanism of an electrical contact material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electric contact analysis, in particular to an in-situ analysis and detection method and device for damage to a surface film of an electric contact. Background Art

[0002] Electrical contacts can be divided into three categories according to their working principles: 1) fixed electrical contacts; 2) rolling and sliding electrical contacts; 3) separable and closeable electrical contacts. Among them, the electrical contact mode in which the two contact elements can be separated and closed at any time is separable and closeable electrical contact, such as the contacts in various switches or relays. The contact elements are usually called contacts or contact points. Contact materials are widely used in various electronic devices. As the core components of electrical switches, relays and circuit breakers, electrical contacts play the role of carrying, connecting and disconnecting currents. Their performance directly determines the reliability, stability and service life of electronic and electrical systems. There are tens of thousands of electrical contacts in modern large and complex systems. Once one or several of them work abnormally or fail, the entire system will be disordered and even cause serious accidents. The losses far exceed the value of the contact elements themselves. For this reason, it is of great significance to study the theory of electrical contacts to improve the working reliability of electrical contacts.

[0003] During the service of the contact material, the contact surface produces very complex interactions. During the opening and closing process of small current electrical contacts, a variety of chemical and physical changes may occur on the surface. First, during the opening and closing process of the electrical contacts, even with small currents, the contact surface may react with oxygen in the air. Because at the moment of contact separation, local high temperature will be generated, making the metal atoms more active. And as the number of openings increases, the oxide layer will continue to accumulate. Second, when the contacts are disconnected, the arc during the opening process (even the relatively weak arc generated by small currents) will have a certain erosion effect on the contact surface. This erosion may change the roughness of the contact surface. Third, the contact surface may absorb impurities in the surrounding environment. During the opening and closing process, due to the electric field and thermal effects, the surrounding gas molecules, dust particles, etc. may be adsorbed on the contact surface. These adsorbed impurities will form a layer of contaminants on the contact surface, affecting the conductivity of the contact, and may further aggravate the wear and corrosion of the contact in subsequent opening and closing operations.

[0004] Therefore, studying the loss of the contact surface film when the contact is in service is of vital importance for understanding the failure and life of electrical devices and avoiding power system failures caused by the degradation of contact performance. It helps to optimize the maintenance plan of electrical equipment. By accurately grasping the change law of the contact surface film, it is possible to determine the reasonable time nodes for inspecting and replacing the contacts, reduce unnecessary maintenance costs and equipment downtime caused by excessive maintenance. In the design stage of electrical equipment, these research results can also guide engineers to choose more suitable contact materials and design more optimized contact structures. For example, according to the changing characteristics of the contact surface film in different environments, a protective layer is designed or the surface treatment process of the contact is improved to improve the stability and reliability of the contact under complex working conditions, thereby extending the service life of electrical devices and enhancing the safety and stability of the entire power system.

[0005] At present, the analysis of contacts is mainly carried out with the help of high-magnification electron microscope and element analysis. For example, patent application CN105424738A discloses a test method for inclusions in electric contact materials based on scanning electron microscope and energy spectrum analysis, and the steps include: (1) Sampling of metallographic samples of electric contact materials, respectively sampling parallel to the working surface of the electric contact materials and perpendicular to the working surface of the electric contact materials; (2) Preparation of metallographic samples of electric contact materials, using inlaying, polishing and etching to obtain metallographic samples; (3) Scanning electron microscope observation of metallographic samples of electric contact materials, under backscattering conditions, the shape, size and number of inclusions in the metallographic samples can be observed; (4) Energy spectrum analysis of metallographic samples of electric contact materials, under backscattering conditions, the composition of inclusions in the metallographic samples can be determined. This analysis method requires the use of professional analysis equipment, which is costly, and requires the preparation of metallographic samples, and the detection cycle is long. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the existing electrical contact detection and to provide an in-situ analysis detection method and device for the damage to the surface film of an electrical contact. The elliptical polarization technology is used to perform in-situ analysis on the surface film damage of an electrical contact for no-load closing and opening of a small current. The surface material changes of the electrical contact during the failure process of the early opening and closing can be accurately detected. The method has the advantages of low cost, fast detection and non-destructiveness.

[0007] Ellipsometry is an accurate, fast and non-destructive optical characterization method, which is extremely sensitive to the surface structure of materials. Using in-situ ellipsometric measurement technology, the film layer of the contact material on the surface of the electrical contact can be tested and analyzed under a variety of different conditions that simulate the electrical contact process, including gas atmosphere, contact pressure, temperature, contact material, voltage and current. With this method, the in-situ failure mode of the surface film of the electrical contact in the early stage can be deeply studied. Based on this, the present application designs a detection method for in-situ failure analysis of early stage electrical contacts, and specially designs a corresponding detection device for in-situ failure analysis of early stage electrical contacts.

[0008] The specific plan is as follows:

[0009] An in-situ analysis and detection method for damage to the surface film of an electric contact comprises the following steps:

[0010] S1. In-situ electrical contact test of electric contacts: placing the electric contacts to be tested into the testing device;

[0011] The detection device includes a control circuit, a polarized light source input and collection device and a sample testing platform, wherein the sample testing platform includes a sealed detection cavity, and transparent optical windows are respectively arranged on opposite sides of the detection cavity; an X-axis sliding bar is installed on the top of the detection cavity, and an X-axis stepping motor is sleeved on the X-axis sliding bar; the X-axis stepping motor is connected to the Z-axis stepping motor, and the Z-axis stepping motor is sleeved on the Z-axis sliding bar; the Z-axis stepping motor is also connected to a circuit module, and the circuit module is connected to a conductive rod, and the end of the conductive rod is connected to a moving contact, and a static contact corresponding to the moving contact is located directly below the moving contact, and a space is reserved below the moving contact for accommodating an electric contact to be detected corresponding to the moving contact, and the electric contact to be detected serves as a static contact;

[0012] Connecting the circuit of the sample test platform, inputting an electrical signal through the circuit module to control the operation of the motor and conducting current to the moving contact through the conductive rod, and adjusting the height and angle of the sample test platform to a suitable position so that the moving contact and the static contact are at the same x-axis position;

[0013] S2, ellipsometry test: polarized light is emitted through the polarized light source input and the acquisition device, and the polarized light is projected onto the electrical contact to be tested through the optical window of the sample test platform, the electrical contact parameters of the electrical contact to be tested are changed, and the ellipsometry parameters Ψ and Δ are tested;

[0014] S3, fitting analysis: constructing a model of the electrical contact to be tested and fitting it, analyzing the fitting results, and calculating the thickness of the film layer in the model;

[0015] S4. Analysis of in-situ failure data of electrical contacts: Analyze the thickness of the film layer under different contact times, and then evaluate the electrical contact test in S1. Further, the electrical contact test adopts a no-load closing and breaking mode. After the circuit of the sample test platform is connected, the contact pressure of the moving contact and the static contact is adjusted to 0.5N. The contact times are 0, 5000, and 10000 times respectively. The breaking frequency is 1Hz, the voltage is set to 3V, and the current upper limit is set to 0.1A. The moving contact and the static contact use resistive loads, the bounce spacing is 5mm, and the contact surface is a circular contact surface with a diameter of 4mm.

[0016] Furthermore, the wavelength of the polarized light in S2 is 200nm-950nm, and the spot size is 200μm×200μm.

[0017] Further, the model in S3 includes an air layer, a rough layer, an organic film layer, an oxide layer and a metal matrix stacked in sequence; or,

[0018] The model includes an air layer, a rough layer, an oxide layer and a metal matrix which are stacked in sequence.

[0019] Furthermore, the metal substrate is fitted by a Drude-Lorentz model, the rough layer is fitted by an Effective Medium Approximation model, the organic film layer is fitted by a Cauchy model, and the oxide film layer is fitted by a Tauc-Lorentz model.

[0020] Furthermore, the calculation method of the film thickness is as follows:

[0021] The mean square error (MSE) is used to judge the fitting effect between the test value and the model fitting value. The least squares iterative fitting analysis is performed through the Levenberg-Marquardt algorithm to control the MSE value between 0.90 and 0.93, and the corresponding film thickness is obtained. The MSE iterative algorithm is as follows:

[0022]

[0023] Where N is the number of fittings of Ψ and Δ, the superscript m represents the test data, and the superscript th represents the fitting data.

[0024] Furthermore, the surface film changes in S4 include: as the number of disconnection and closing times increases, the oxide layer on the surface of the electrical contact becomes thicker and the roughness increases.

[0025] Furthermore, the surface film changes in S4 include: as the electric field strength increases, the oxide layer on the surface of the electrical contact breaks and the roughness increases.

[0026] The present invention also protects the in-situ analysis and detection method of the damage to the surface film of the electric contact, and the in-situ analysis and detection device of the damage to the surface film of the electric contact, which includes a control circuit, a polarized light source input and collection device and a sample testing platform, wherein the sample testing platform includes a sealed detection cavity, and transparent optical windows are respectively arranged on two opposite sides of the detection cavity; an X-axis sliding bar is installed on the top of the detection cavity, and an X-axis stepping motor is sleeved on the X-axis sliding bar; the X-axis stepping motor is connected to the Z-axis stepping motor, and the Z-axis stepping motor is sleeved on the Z-axis sliding bar; the Z-axis stepping motor is also connected to a circuit module, and the circuit module is connected to a conductive rod, and the end of the conductive rod is connected to a moving contact, and space is reserved below the moving contact for accommodating an electrical contact to be detected corresponding to the moving contact.

[0027] Beneficial effects: The present invention adopts non-contact in-situ spectral testing technology to accurately, quickly, non-destructively and in real time detect the early in-situ failure process of electrical contacts, providing equipment means and experimental basis for the study of the early failure mechanism of electrical contact materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings will be briefly introduced below. Obviously, the accompanying drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.

[0029] Figure 1 It is a technical roadmap provided by an embodiment 1 of the present invention;

[0030] Figure 2 This is a schematic diagram of the principle of a device provided by Embodiment 1 of the present invention;

[0031] Figure 3 is a cross-sectional view of a sample testing platform provided in Example 1 of the present invention;

[0032] Figure 4 is a stereoscopic diagram of a sample testing platform provided in Embodiment 1 of the present invention;

[0033] Figure 5 This is a graph showing the Δ result of an ellipsometric test of an Ag-based contact material under different contact times provided in Example 1 of the present invention;

[0034] Figure 6 This is a graph showing the ψ result of an ellipsometry test of an Ag-based contact material under different contact times provided in Example 1 of the present invention;

[0035] Figure 7 This is a diagram of the physical structure model of the ellipsometry of the Ag-based contact material in the breaking and closing mode provided by Example 1 of the present invention;

[0036] Figure 8This is a graph showing the Δ result of an ellipsometry test of an Ag-based contact material under different contact times provided in Example 2 of the present invention;

[0037] Fig. 9 This is a graph showing the ψ result of an ellipsometry test of an Ag-based contact material under different contact times provided in Example 2 of the present invention;

[0038] Fig.10 This is a diagram of the physical structure model of the ellipsometry of the Ag-based contact material in the disconnected and closed modes provided in Example 2 of the present invention. DETAILED DESCRIPTION

[0039] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.

[0040] Example 1

[0041] An in-situ analysis and detection method for damage to the surface film of an electrical contact, the technical route of which is as follows Figure 1 As shown, it includes in-situ electrical contact testing of electric contacts, ellipsometry testing (adjusting electrical contact parameters of contacts in ellipsometry testing), fitting analysis and in-situ failure data analysis of electric contacts.

[0042] The following describes the device used in the detection method, which includes a sample test platform, a control circuit, a polarized light source input and a collection device. Figure 2 As shown, when in use, a light source is input to the sample test platform, and the electric contacts are controlled by a control circuit, thereby collecting electrical signals and polarized light signals, and further analyzing and obtaining data.

[0043] Specifically, the control circuit includes: a power supply module for the power input part, and a control circuit module, wherein the control circuit uses an AT8236 dual-channel drive module, model D157B, which drives a CCM brand model W50-25 stepper motor module, with an effective stroke of 30mm, and can drive a dual-axis motor to make forward and reverse stepless adjustments. The conductive rod power supply module uses an AC-DC step-down isolation power supply module with a product model of AM31-12W12C, with an input of 220V AC voltage and a DC output of 5-30V.

[0044] The polarized light source input and collection device includes: a light source input end and a collection end.

[0045] The sample test platform includes: dual-axis stepper motor and sliding rod, circuit module, conductive rod, moving and static contacts, etc. Figure 3 and Figure 4 A structural schematic diagram of the sample testing platform is specifically given, including a sealed detection cavity, and transparent optical windows are respectively arranged on the opposite sides of the detection cavity, so as to inject light signals and detect light signals. An X-axis slide bar is installed on the top of the detection cavity, and an X-axis stepper motor is sleeved on the X-axis slide bar; the X-axis stepper motor is connected to the Z-axis stepper motor, and the Z-axis stepper motor is sleeved on the Z-axis slide bar. The Z-axis stepper motor is also connected to the circuit module, and the circuit module is connected to the conductive rod. The end of the conductive rod is connected to the moving contact, and the static contact corresponding to the moving contact is located directly below the moving contact. When the above-mentioned detection device is working, the circuit module is driven to move along the X-axis slide bar by the X-axis stepper motor, and the circuit module can also be driven to move along the Z-axis slide bar by the Z-axis stepper motor, thereby driving the moving contact to move in the X direction and the Z direction respectively.

[0046] In the above device, the x-axis stepper motor is used to adjust the moving and static contacts to the same x-axis position, the z-axis stepper motor is used to realize the contact separation and closing process, the circuit module is used to input electrical signals to control the operation of the motor and conduct current to the moving contact through the conductive rod, and the static contact is the contact sample to be tested. The circuit module control circuit adopts the AT8236 dual-channel drive module, model D157B, which drives the CCM brand model W50-25 stepper motor module, with an effective stroke of 30mm, and can drive the dual-axis motor to adjust forward and reverse steplessly. The conductive rod power supply module adopts the AC-DC step-down isolation power supply module with product model AM31-12W12C, which inputs 220V AC voltage and outputs 5-30V DC.

[0047] The specific detection process is described below. The detection object Ag-based contact material is a commercially available product. The steps include:

[0048] 1. Electrical contact test

[0049] The electrical contact process of Ag-based contact materials was studied under the no-load closing and breaking mode. The atmosphere in the cavity was adjusted to air, the contact pressure was adjusted to 0.5N, the number of contacts was 0, 5000 (5k), and 10000 (10k), the breaking frequency was 1Hz, the voltage was set to 3V, the current upper limit was set to 0.1A, the moving and static contacts adopted resistive loads, the bounce spacing was 5mm, and the contact surface was a circular contact surface with a diameter of 4mm.

[0050] 2. Ellipsometry test

[0051] The ellipsometry test is adopted, the measurement range is (200nm-950nm), and the spot size is 200μm×200μm. The light source device is placed outside the detection device, and the generated light spot enters through the optical window of the detection device and irradiates onto the contact.

[0052] After adjusting the electrical contact parameters of the contacts and conducting experiments with different contact times, the ellipsometric parameters Ψ (i.e. Psi) and Δ (i.e. Delta) were tested respectively. Figure 5 and Figure 6 shown.

[0053] It can be seen that the different contact times have the following rules: at 0 contacts, Delta has a peak value at around 325nm, while Psi rises rapidly in the range of 300-400nm and then tends to decline slowly; at 5k contacts, Delta drops rapidly from 300 to 50 in the range of 300-350nm and then tends to be flat, Psi rises relatively rapidly in the range of 200-300nm and reaches a maximum value at 310nm; at 10k contacts, Delta has a peak and valley at around 325nm, and then there is an upward process with a decreasing growth rate as the wavelength increases. The change trend of Psi is similar to that of 0 contacts, but the values ​​are generally small.

[0054] 3. Fitting analysis

[0055] In order to further interpret the psi and delta data, a suitable physical structure model is constructed according to the contact material type to fit the physical changes of the contact surface film, such as Figure 7 As shown, a structural model of air layer-rough layer-organic film layer-oxide layer-Ag-based contact substrate stacking is constructed in sequence.

[0056] The metal substrate is fitted by the Drude-Lorentz model; the surface roughness of the metal substrate is simulated by the Effective Medium Approximation (EMA) model; the organic film layer is fitted by the Cauchy model; the oxide layer is fitted by the Tauc-Lorentz model; MSE (mean square error) is used to judge the fitting effect between the test value and the fitting value, and the least squares iterative fitting analysis is performed by the Levenberg-Marquardt algorithm to control the MSE value within a reasonable value, and obtain the corresponding optical constant value and thickness d value. The MSE iterative algorithm is as follows:

[0057]

[0058] Where N is the number of fittings of Ψ and Δ, the superscript m represents the test data, and the superscript th represents the fitting data.

[0059] The thickness d value is obtained from the Fresnel reflection coefficient formula, and the algorithm is as follows:

[0060]

[0061] Where d is the thickness of the fitted film, n2 is the refractive index of the film, n1 is the refractive index of the underlying material, and φ1 is the incident angle.

[0062] The models used in the above fitting process are all existing classical physical models, such as the Drude-Lorentz model fitting, also known as the Drude model, which assumes that the microscopic performance of electrons in solids can be treated by classical methods, much like a spike ball machine, in which electrons constantly bounce back and forth between heavier, relatively fixed positive ions. The EMA model, or effective medium approximation model, is a theoretical method widely used in fields such as physics and materials science. It is mainly used to describe the dielectric constant of composite materials composed of two or more different materials. The Cauchy model is a mathematical model mainly used to describe the optical properties of materials, especially the dispersion relation of materials, that is, the relationship between the refractive index of materials and wavelength. The Tauc-Lorentz model is a semi-empirical model used to describe the relationship between the absorption coefficient of materials and the energy of photons. It comprehensively considers the band gap of the material and the light absorption process caused by factors such as interband transitions and exciton effects. Compared with the classical Drude model (mainly used to describe the optical properties of metals), the Tauc-Lorentz model is more suitable for semiconductors and insulating materials. The Levenberg-Marquardt algorithm is an optimization algorithm for solving nonlinear least squares problems. It combines the advantages of the gradient descent method and the Gauss-Newton method, and introduces a damping factor λ to balance the search direction and step size, thereby dynamically adjusting the behavior of the algorithm during the iteration process. When λ is larger, the algorithm is closer to the gradient descent method, with smaller steps but a more stable direction; when λ is smaller, the algorithm is closer to the Gauss-Newton method, with larger steps but a more accurate direction.

[0063] 4. In-situ failure data of electrical contacts

[0064] The electrical contact parameters in the above analysis process were recorded and plotted, and the ellipsometry fitting results were recorded and plotted, and finally the in-situ thickness changes d1, d2, d3, and d4 were obtained. The results are shown in Table 1:

[0065] Table 1 Surface layer thickness of Ag-based contact materials at different contact times

[0066]

[0067] As can be seen from Table 1, when the contact material gradually increases with the number of contacts, in the initial stage of electrical contact, the organic film layer on the contact surface is damaged due to mechanical action, and the thickness decreases from 6.44nm before breaking and closing to 1.36nm after 10k breaking and closing. At the same time, pollutants with poor conductivity are generated on the contact surface, causing the thickness of the oxide on the contact surface to increase from 0nm to 7.43nm at 5k times, and then to 8.29nm at 10k times. When the number of contacts reaches a certain value, the contact surface is plastically deformed, causing the contact surface material to mix with the pollutants, reducing the erosion rate. On the one hand, the contact area is increased to reduce the contact resistance, and on the other hand, the mixing with the original material increases the contact resistance. The change in contact resistance causes the change in the internal electric field of the material, affecting the response to the spectrum. In general, the Psi value falls back to below the time of 0 contacts, and maintains the wavelength change law at the initial contact.

[0068] From the above data, it can be seen that during the opening and closing process of small current electrical contacts, as the number of opening and closing times increases, physical structural changes such as thickening of the oxide film and increased roughness occur on the surface.

[0069] Example 2

[0070] In Example 1, because the organic film plays a certain protective role on the metal surface of the contact, in order to study the change of the surface of the electric contact with voltage, this example uses an electric contact without organic film treatment to conduct experiments. The electric contact without organic film treatment is a commercially available product, and the detection device is the same as in Example 1. The specific process is as follows:

[0071] 1. Electrical contact test

[0072] The electrical contact process of Ag-based contact materials was studied under the no-load closing and breaking mode. The atmosphere in the cavity was adjusted to air, the contact pressure was adjusted to 0.5N, the number of contacts was 1000 times, the breaking frequency was 1Hz, the voltage was set to 3, 6, 9, and 12V, the current upper limit was set to 0.1A, the moving and static contacts used resistive loads, the bounce spacing was 5mm, and the contact surface was a circular contact surface with a diameter of 4mm.

[0073] 2. Ellipsometry test

[0074] The ellipsometry parameters Ψ and Δ were measured by using ellipsometry spectroscopy and recording the metallographic images under an optical microscope. Figure 8 , Fig. 9 As shown in the figure, the contact Delta value under different voltages generally decreases first and then increases with the wavelength, and the value is the largest at 3 V. For the Psi value, it generally shows a rapid upward trend in the range of 350-400 nm. Compared with Delta, the contact voltage has a greater impact on Psi, with the lowest Psi at 9 V and the maximum at 12 V.

[0075] 3. Fitting analysis

[0076] Build a suitable physical structure model according to the contact material type, see Fig.10 , and sequentially construct a structural model of air-rough layer-oxide layer-inner interface layer-Ag-based metal matrix stacking.

[0077] The Ag-based metal matrix is ​​fitted using the Drude-Lorentz model; the Effective Medium Approximation (EMA) model is used to simulate the rough and rough layers of the gold inner interface layer; the Tauc-Lorentz model is used for the oxide layer; and MSE (mean square error) is used to judge the fitting effect between the test value and the fitting value. The specific process is the same as in Example 1.

[0078] 4. In-situ failure data of electrical contacts

[0079] The electrical contact parameters in the above analysis process were recorded and plotted, and the ellipsometry fitting results were recorded and plotted, and finally the in-situ thickness changes d1, d2, d3, and d4 were obtained. The results are shown in Table 2:

[0080] Table 2 Surface layer thickness of Ag-based contact materials at different voltages

[0081]

[0082]

[0083] As can be seen from Table 2, with the increase of contact current (voltage), the roughness of the contact surface increases significantly, indicating that the surface has a certain degree of wear. The oxide layer exists, and its thickness decreases significantly with the increase of voltage, from 4.05nm to 0.13nm at 12V. This shows that there are indeed some oxide-composed pollutants on the contact surface, and the thickness of this oxide layer has a certain relationship with the applied voltage and current. Pollutants are the product of the interaction between the surrounding environment and the contact metal material, so the pollutants are usually different from the original material of the contact, and the measuring current has a melting and destructive effect on the pollutants. The larger the measuring current, the more obvious the melting and breakdown effect on the film, so the thickness of this oxide film layer decreases with the increase of voltage. High contact voltage will cause the oxide film layer on the contact surface to grow and destroy continuously, accelerate the wear and aging of the contact material, and thus shorten the service life of the contact.

[0084] From the above data, it can be seen that during the opening and closing process of small current electrical contacts, as the electric field strength increases, physical structural changes such as oxide film rupture and thinning, and increased roughness occur on the surface.

[0085] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0086] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0087] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. An in-situ analysis and detection method for damage to the surface film of an electric contact, characterized in that: The following steps are involved: S1. In-situ electrical contact test of electric contacts: placing the electric contacts to be tested into the testing device; The detection device includes a control circuit, a polarized light source input and collection device and a sample testing platform, wherein the sample testing platform includes a sealed detection cavity, and transparent optical windows are respectively arranged on opposite sides of the detection cavity; an X-axis sliding bar is installed on the top of the detection cavity, and an X-axis stepping motor is sleeved on the X-axis sliding bar; the X-axis stepping motor is connected to the Z-axis stepping motor, and the Z-axis stepping motor is sleeved on the Z-axis sliding bar; the Z-axis stepping motor is also connected to a circuit module, and the circuit module is connected to a conductive rod, and the end of the conductive rod is connected to a moving contact, and a static contact corresponding to the moving contact is located directly below the moving contact, and a space is reserved below the moving contact for accommodating an electric contact to be detected corresponding to the moving contact, and the electric contact to be detected serves as a static contact; Connecting the circuit of the sample test platform, inputting an electrical signal through the circuit module to control the operation of the motor and conducting current to the moving contact through the conductive rod, and adjusting the height and angle of the sample test platform to a suitable position so that the moving contact and the static contact are at the same x-axis position; S2, ellipsometry test: polarized light is emitted through the polarized light source input and the acquisition device, and the polarized light is projected onto the electrical contact to be tested through the optical window of the sample test platform, the electrical contact parameters of the electrical contact to be tested are changed, and the ellipsometry parameters Ψ and Δ are tested; S3, fitting analysis: constructing a model of the electrical contact to be tested and fitting it, analyzing the fitting results, and calculating the thickness of the film layer in the model; S4. In-situ failure data analysis of electrical contacts: analyzing the film thickness at different contact times, and then evaluating the changes in the surface film of the electrical contacts to be tested.

2. The in-situ analysis and detection method for the damage of the surface film of the electric contact according to claim 1, characterized in that: The electrical contact test in S1 adopts a no-load closing and breaking mode. After the circuit of the sample test platform is connected, the contact pressure of the moving contact and the static contact is adjusted to 0.5N, the number of contacts are 0, 5000, and 10000 times respectively, the breaking frequency is 1Hz, the voltage is set to 3V, and the current upper limit is set to 0.1A. The moving contact and the static contact use resistive loads, the bounce spacing is 5mm, and the contact surface is a circular contact surface with a diameter of 4mm.

3. The in-situ analysis and detection method for the damage of the surface film of the electric contact according to claim 2, characterized in that: The wavelength of the polarized light in S2 is 200nm-950nm, and the spot size is 200μm×200μm.

4. The in-situ analysis and detection method for the damage of the surface film of the electric contact according to any one of claims 1 to 3, characterized in that: The model in S3 includes an air layer, a rough layer, an organic film layer, an oxide layer and a metal substrate stacked in sequence; or, The model includes an air layer, a rough layer, an oxide layer and a metal matrix which are stacked in sequence.

5. The in-situ analysis and detection method for the damage of the surface film of the electric contact according to claim 4, characterized in that: The metal substrate is fitted by the Drude-Lorentz model, the rough layer is fitted by the Effective Medium Approximation model, the organic film layer is fitted by the Cauchy model, and the oxide film layer is fitted by the Tauc-Lorentz model.

6. The in-situ analysis and detection method for the damage of the surface film of the electric contact according to claim 5, characterized in that: The calculation method of the film thickness is as follows: The mean square error (MSE) is used to judge the fitting effect between the test value and the model fitting value. The least squares iterative fitting analysis is performed through the Levenberg-Marquardt algorithm to control the MSE value between 0.90 and 0.93, and the corresponding film thickness is obtained. The MSE iterative algorithm is as follows: Where N is the number of fittings of Ψ and Δ, the superscript m represents the test data, and the superscript th represents the fitting data.

7. The in-situ analysis and detection method for the damage of the surface film of the electric contact according to claim 4, characterized in that: The surface film changes in S4 include: as the number of disconnection and closing times increases, the oxide layer on the surface of the electrical contact becomes thicker and the roughness increases.

8. The in-situ analysis and detection method for the damage of the surface film of the electric contact according to claim 4, characterized in that: The surface film changes in S4 include: as the electric field strength increases, the oxide layer on the surface of the electrical contact breaks and the roughness increases.

9. An in-situ analysis and detection device for electric contact surface film damage using the in-situ analysis and detection method for electric contact surface film damage according to any one of claims 1 to 8, characterized in that: It includes a control circuit, a polarized light source input and collection device, and a sample testing platform, wherein the sample testing platform includes a sealed detection cavity, and transparent optical windows are respectively arranged on two opposite sides of the detection cavity; an X-axis sliding bar is installed on the top of the detection cavity, and an X-axis stepping motor is sleeved on the X-axis sliding bar; the X-axis stepping motor is connected to the Z-axis stepping motor, and the Z-axis stepping motor is sleeved on the Z-axis sliding bar; the Z-axis stepping motor is also connected to a circuit module, and the circuit module is connected to a conductive rod, and the end of the conductive rod is connected to a moving contact, and space is reserved under the moving contact for accommodating an electrical contact to be detected corresponding to the moving contact.

Citation Information

Patent Citations

  • Method for testing inclusions in electric contact material on basis of scanning electron microscope and energy spectrum analysis

    CN105424738A

Cited By

  • Electronic connector with anti-falling structure

    CN122370807A

  • Electronic connector with anti-dropping structure

    CN122370807B